2012
DOI: 10.1007/s11427-012-4322-y
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal chromatin proteins

Abstract: Archaea, along with Bacteria and Eukarya, are the three domains of life. In all living cells, chromatin proteins serve a crucial role in maintaining the integrity of the structure and function of the genome. An array of small, abundant and basic DNA-binding proteins, considered candidates for chromatin proteins, has been isolated from the Euryarchaeota and the Crenarchaeota, the two major phyla in Archaea. While most euryarchaea encode proteins resembling eukaryotic histones, crenarchaea appear to synthesize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 67 publications
3
21
0
Order By: Relevance
“…Other upregulated replication and transcription genes included those encoding reverse gyrase, a TFIIB paralog, the M subunit of RNAP, and a putative transcriptional regulator. The gene encoding Sso7d was also upregulated in STIV-infected cells, consistent with the proposed role for the chromatin protein in viral DNA packaging (118). STIV appears to share limited but potentially interesting similarity to SSV2 in eliciting a host response to infection.…”
Section: Figsupporting
confidence: 72%
“…Other upregulated replication and transcription genes included those encoding reverse gyrase, a TFIIB paralog, the M subunit of RNAP, and a putative transcriptional regulator. The gene encoding Sso7d was also upregulated in STIV-infected cells, consistent with the proposed role for the chromatin protein in viral DNA packaging (118). STIV appears to share limited but potentially interesting similarity to SSV2 in eliciting a host response to infection.…”
Section: Figsupporting
confidence: 72%
“…Sso7d, a member of the Sul7d family, is one of the major chromatin proteins responsible for chromosome organization in Sulfolobus (65). This small basic protein is known to bind dsDNA nonspecifically and induces negative supercoiling (83) as well as compaction of relaxed or positively supercoiled DNA in vitro (64).…”
Section: Discussionmentioning
confidence: 99%
“…3A and B). Sso7d is a small, basic protein, which belongs to the extensively studied Sul7d family of 7-kDa DNA-binding proteins and represents one of the major chromatin proteins of Sulfolobus solfataricus (64,65). Notably, SDS-PAGE analysis of fractions collected from the CsCl gradient showed that Sso7 is exclusively detected in the fraction containing SSV1 virions.…”
Section: Aggregation Of Ssv1 Particles Is Modulated By Ionic and Hydrmentioning
confidence: 99%
“…Thus, it is possible that PolB activity was substantially underestimated at 50 o C. Euryarchaea also appear to differ from crenarchaea in genome packaging. While the former encode archaeal histones, the latter employ unique chromatin proteins, such as Cren7 and Sul7d (Zhang et al, 2012). Despite their differences in sequence and structure, these archaeal chromatin proteins behaved in a similar fashion in modulating strand displacement.…”
Section: Discussionmentioning
confidence: 99%